Metacognitive and Social Strategies to Promote EFL learners’ Lecture Comprehension - Al Zumor, Abdul Wahed Qasem (Journal of History Culture and Art Research, 2019)
This study attempts to explore the challenges that influence academic lecture listening comprehension of Saudi EFL students. Seventy-five students majoring in English participated in the diagnostic stage. In the next stage, 15 students underwent some intervention for 6 weeks where metacognitive and social strategies in teaching were incorporated. Later, the participants were interviewed in a semi-structured setting where they were asked to reflect on the experiment. The major findings of the study indicate that the factors that affect students’ listening comprehension pertain to teachers and teaching, students themselves, content of the courses and the program itself. The study recommends a paradigm shift in the teaching methods that focus on metacognitive and social strategies as suggested in the experiment. Furthermore, students’ linguistic and communication proficiency should be given special care. Moreover, training the EFL students in academic lecture listening comprehension strategies is highly recommended to be incorporated into the program design.